2023
DOI: 10.1038/s41598-023-43689-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of ensemble machine learning approach to assess the factors affecting size and polydispersity index of liposomal nanoparticles

Benyamin Hoseini,
Mahmoud Reza Jaafari,
Amin Golabpour
et al.

Abstract: Liposome nanoparticles have emerged as promising drug delivery systems due to their unique properties. Assessing particle size and polydispersity index (PDI) is critical for evaluating the quality of these liposomal nanoparticles. However, optimizing these parameters in a laboratory setting is both costly and time-consuming. This study aimed to apply a machine learning technique to assess the impact of specific factors, including sonication time, extrusion temperature, and compositions, on the size and PDI of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…The ζ-potential results reported in Table S2 showed that all nanoparticles exhibited a very low negative surface charge, which suggests that the NIR dyes mainly residing at the surface of the nanomaterials. All three INMs also exhibit a polydispersity index less than 0.30 (Table S2), which indicates a homogeneous population of the nanodrug. , [DOX]­[ICG] exhibited the lowest PDI, whereas [DOX]­[IR783] depicted the highest PDI, which is attributed to its lowest ζ-potential value. Dynamic light scattering (DLS) experiments were performed at various intervals to test the stability of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The ζ-potential results reported in Table S2 showed that all nanoparticles exhibited a very low negative surface charge, which suggests that the NIR dyes mainly residing at the surface of the nanomaterials. All three INMs also exhibit a polydispersity index less than 0.30 (Table S2), which indicates a homogeneous population of the nanodrug. , [DOX]­[ICG] exhibited the lowest PDI, whereas [DOX]­[IR783] depicted the highest PDI, which is attributed to its lowest ζ-potential value. Dynamic light scattering (DLS) experiments were performed at various intervals to test the stability of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the average size of ca. 160 nm allows the permeation of oleosomes through the skin, while the PDI values less than or equal to 0.2 demonstrated a narrow size distribution …”
Section: Resultsmentioning
confidence: 99%
“…160 nm allows the permeation of oleosomes through the skin, 32 while the PDI values less than or equal to 0.2 demonstrated a narrow size distribution. 33 The presence of Npx or Ica, or both drugs, in oleosomes did not significantly modify the size or PDI, thus endorsing the lack of physical destabilization due to the drugs' loading. The zeta potential of oleosomes was below −50 mV for all the resulting nanovesicles due to the presence of the oleic acid carboxylic moiety on their surface, thus suggesting a proper electrostatic repulsion that stabilized oleosomes and prevented their aggregation in the dispersion medium.…”
Section: ■ Experimental Sectionmentioning
confidence: 92%
“…To measure the variance amongst the actual and expected outcomes for each observation, the mean square error, or MSE, is employed. The model's predicted values and actual values are quantified by the mean absolute error (MAE), which measures the average absolute difference between them [6,39].…”
Section: Evaluation Matrixmentioning
confidence: 99%
“…Particle size and particle density index (PDI), two crucial metrics for evaluating a drugloaded nanoparticle formulation, depend on a number of factors such as composition, the duration of sonication, and extrusion temperature. For achieving an ideal particle size with a narrow size distribution, empirical methods are often employed to adjust these independent parameters through iterative trial-and-error methodology [6].…”
Section: Introductionmentioning
confidence: 99%